Global, regional, and national burden of cataract: A comprehensive analysis and projections from 1990 to 2021 - Lixia Lin; Yongshun Liang; Guiyang Jiang; Qingqiao Gan; Tianqi Yang; Peipei Liao; Hao Liang (PLoS ONE, 2025)
Objective Cataract is the most prevalent cause of blindness. Surgery remains the only effective and widely accepted treatment; early diagnosis and intervention can significantly prevent blindness. Hence,Understanding the current epidemiological status of cataract is crucial for formulating better healthcare policies and effectively preventing blindness due to cataract. Design This study utilizes Global burden of Disease (GBD) 2021 data to conduct an in-depth analysis of the burden of cataract from 1990 to 2021, including gender disparities, risk factors, and the relationship between Socio-Demographic index (SDI) and disease burden. Additionally, we performed a frontier analysis of Disability-Adjusted Life Years (DALYs) due to cataract from 1990 to 2021. Finally, we used the BAPC model to project the burden of cataract by gender from 2022 to 2030. Results The study revealed that the global burden of cataract remains significant. Worldwide, the Estimate Annual Percentage Change (EAPC) for cataract prevalence was 0.2117([95% CI] 0.1172–0.3063); the EAPC for cataract DALYs is −0.4798([95%CI] −0.5766--0.3828). Predominantly affecting females, individuals aged 50 and older, and those in medium-low and low SDI regions. Furthermore, the Bayesian Age-Period-Cohort (BAPC) model forecast a gradual decline in the global burden of cataract over the next nine years. Conclusion This study utilized GBD 2021 to provide an in-depth analysis of the current global disease burden of cataracts. The results showed that although the Age-Standardized Rate (ASR) of DALYs decreased, the overall cataract Number still showed an increasing trend from 1990 to 2021 and 2022–2030.